2007
DOI: 10.1111/j.1467-7652.2007.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐yield rapid production of hepatitis B surface antigen in plant leaf by a viral expression system

Abstract: SummaryRecombinant hepatitis B surface antigen (HBsAg) constitutes currently used vaccines against hepatitis B virus, and has been successfully employed as a carrier for foreign epitopes.With the aim of developing an inexpensive, easily administered vaccine source for global immunization, several groups have expressed HBsAg in plant systems. Transgenic plant-derived HBsAg assembles into virus-like particles (VLPs) and is immunogenic in both mice and humans. However, HBsAg expression is relatively low in transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 39 publications
(96 reference statements)
0
49
0
Order By: Relevance
“…Plant-expressed S-HBsAg had buoyant density comparable to the antigen from human plasma or recombined in yeast [35,45,49,52,54,56,58]. Western blot analyses showed that S-HBsAg in plant cell was of proper size of 24 kDa and non-glycosylated, similarly to the yeast-derived antigen [41,46,50,51,59,71]. Yet, glycosylation of S-HBsAg as well as M and L antigens in plants was also reported [54,56,67,70], although putatively the antigens were modified according to the plant glycosylation pattern.…”
Section: Production Of Hbv Antigens In Plant Sys-temsmentioning
confidence: 94%
“…Plant-expressed S-HBsAg had buoyant density comparable to the antigen from human plasma or recombined in yeast [35,45,49,52,54,56,58]. Western blot analyses showed that S-HBsAg in plant cell was of proper size of 24 kDa and non-glycosylated, similarly to the yeast-derived antigen [41,46,50,51,59,71]. Yet, glycosylation of S-HBsAg as well as M and L antigens in plants was also reported [54,56,67,70], although putatively the antigens were modified according to the plant glycosylation pattern.…”
Section: Production Of Hbv Antigens In Plant Sys-temsmentioning
confidence: 94%
“…In this case, the transient expression system using plant virus-based vectors have the advantage of rapid high-level expression of the recombinant protein as compared with stable transgenic plants. Recent work has demonstrated that tobacco leaves infiltrated with MagnlCON viral vectors produced HBsAg at a high level (~300 µg/g fresh leaf weight) on day 10 after infection [40], which exceeds the best results achieved for transgenic plants by several times (TABle 1). It was demonstrated that transiently expressed HBsAg was correctly assembled and was immunogenic in intraperitoneally injected mice.…”
Section: Reviewmentioning
confidence: 96%
“…When using plants as alternative expression systems for accumulation of antigens, the work is also directed towards an increase in the yield of recombinant protein in plant tissues [40,47,49]. In this case, the transient expression system using plant virus-based vectors have the advantage of rapid high-level expression of the recombinant protein as compared with stable transgenic plants.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…An incomplete backcross and hybrid breeding program has already produced material that expresses upward of 500 μg/g (unpublished data) and therefore shows exceptional promise as a candidate oral vaccine. Nicotiana benthamiana, using the transient MagnICON viral vector system, has averaged 295 μg/g of fresh weight (Huang et al 2008), but this system is designed for purification and injection of the antigen, rather than oral delivery. Nicotiana species typically produce noxious secondary compounds that are not compatible with an oral delivery system and therefore are not good candidates for oral vaccines in an unpurified form.…”
Section: Expression Level Of Hbsag In Edible Tissues and Response In mentioning
confidence: 99%